Achieving comprehensive disease control in patients with early and established rheumatoid arthritis treated with adalimumab plus methotrexate versus methotrexate alone. Issue 2 (26th September 2017) - Keystone, Edward C; Breedveld, Ferdinand C; Heijde, Désirée van der; van Vollenhoven, Ronald F; Emery, Paul; Smolen, Josef S; Sainsbury, Iain; Florentinus, Stefan; Kupper, Hartmut; Chen, Kun; Kavanaugh, Arthur
Abstract : Objective: To evaluate the achievement of comprehensive disease control (CDC) following 1 year of treatment with adalimumab+methotrexate versus methotrexate alone and whether early achievement of remission (at week 24 or 26) is associated with CDC at week 52 in patients with either early or established rheumatoid arthritis (RA). Methods: Post hoc analyses were conducted in three clinical studies assessing treatment with adalimumab+methotrexate: DE019 (NCT00195702 ) enrolled patients with established RA who were methotrexate inadequate responders; OPTIMA (NCT00420927 ) and PREMIER (NCT00195663 ) enrolled methotrexate-naive patients with early RA. In OPTIMA, patients not achieving stable low disease activity at weeks 22 and 26 in the placebo+methotrexate group could receive open-label adalimumab+methotrexate for 52 weeks (Rescue ADA arm). CDC was defined as the simultaneous achievement of clinical remission (DAS28(CRP)<2.6), normal function (HAQ-DI<0.5) and absence of radiographic progression (ΔmTSS≤0.5). Results: Regardless of disease duration, significantly more patients receiving adalimumab+methotrexate achieved CDC compared with methotrexate alone. In the adalimumab+methotrexate group, a numerically greater proportion of patients with early RA (~25%) versus established RA (14%) achieved CDC at 1 year; achievement of CDC was notably greater among patients who met criteria for remission at week 24 or 26 (~50% of patients with early RA and 39% with established RA). Conclusion: Treatment with adalimumab+methotrexate increases the likelihood of achieving CDC in patients with either early or established RA. Clinical remission at week 24 or 26 is associated with achievement of CDC at week 52. Trial registration number: DE019 (NCT00195702 ), OPTIMA (NCT00420927 ), PREMIER (NCT00195663 ); Post-results.